Prins Cyclization Using Magnesium Halides: Mild Access to 4-Halogenated Polysubstituted Tetrahydropyrans with a Special Feature - Walter, Mario; Schinzer, Dieter (Synlett, 2014)
Different 4-halo-substituted polyfunctionalized tetrahydropyrans were easily synthesized by segment-coupling Prins cyclization utilizing magnesium halides. The moderate Lewis acidity allows transformation of substrates bearing acid-labile functional groups. A solvent dependency of the stereochemistry at the C4 carbon was observed.
Keywords: Prins cyclization; magnesium halides; halogenated tetrahydropyrans; solvent-dependent stereochemistry; polysubstituted tetrahydropyrans